The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1757-899x/883/1/012161
|View full text |Cite
|
Sign up to set email alerts
|

Drying agent spreading in stack of drying material

Abstract: This article analysis of drying agent’s spreading in ventilated drying of stem type agricultural crops and vegetable seeds, through which it aims to produce more and more high-quality products. The similar drying was not observed in different parts of the crops in ventilated drying, some parts of the drying product were dried out but some parts not dried well. The aims of the paper study this process. Therefore, products must be placed in the dryer with the thickness to have each point dry at the same time. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…To study the soaking process, a special container was made with a sieve set at different depths. The study was carried out according to the method described in [1][2][3][4][5]. As a criterion for the assessment, the relative humidity of the pollution was used, after a certain time.…”
Section: Methodsmentioning
confidence: 99%
“…To study the soaking process, a special container was made with a sieve set at different depths. The study was carried out according to the method described in [1][2][3][4][5]. As a criterion for the assessment, the relative humidity of the pollution was used, after a certain time.…”
Section: Methodsmentioning
confidence: 99%
“…During this period, the bender travels a distance у 1 +у 2 and assumes the position Е 1 С 1 . The number of bent cotton stalks n during displacement у 1 +у 2 can be determined as follows [18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the number and type of equipment performing technological processes are increasing, and their entry and exit into the field correspondingly increase. This leads to compaction and deterioration of the structure of the soil, in addition to not meeting the requirements of resource conservation [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of reusing cotton bolls as organic fertilizer began in 1913 in the cotton industry of Uzbekistan. A.E.Vyalovsky, D.A.Sabinin, F.A.Skryabin, E.Ya.Yasheva, G.I.Yarovenko, and A.G.Shalimov studied the length, depth of burial, rotting process, and factors affecting it [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the yield of cultivated cotton increased by 4.1 centners, and the soil density in the fields where cotton was buried decreased by 30-40% when measured after three years [5][6]. Studies have recommended burying the stalks by crushing them, spreading them over the field, and then plowing them in with plows [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%